Analysis of Fatwas of Scholars Mentioned in Sirajuddin al-Ushi's Work "Al-Fatawa as-sirajiya" (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article provides a comprehensive analysis of the fatwas mentioned in Sirajuddin al-Ushi's work "Fatawai Sirojiya," focusing on the Hanafi school of thought. It explores al-Ushi's methodology, emphasizing his reliance on the opinions of foundational Hanafi scholars, his classification as a mujtahid of tarjih level, and his detailed references to various sources within Islamic jurisprudence. The analysis highlights al-Ushi's contributions to Hanafi jurisprudence, his scholarly approach to issuing fatwas, and the extensive network of sources he engaged with, ranging from the founders of the Hanafi madhhab to contemporaries across various Islamic schools of thought.The article delves into the intricacies of Islamic jurisprudence as practiced by Sirajuddin al-Ushi, showcasing his deep engagement with previous scholarship within the Hanafi school and his judicious application of these teachings to issue fatwas. It underscores the rich tapestry of Islamic legal thought and the importance of understanding the historical and scholarly context in which these fatwas were formulated. The analysis sheds light on the dynamic nature of Islamic jurisprudence, where scholars like al-Ushi navigate between tradition and the contemporary needs of their community, contributing to the ongoing development of Islamic law.